2022
DOI: 10.1186/s40694-022-00145-8
|View full text |Cite
|
Sign up to set email alerts
|

Variability in metabolites produced by Talaromyces pinophilus SPJ22 cultured on different substrates

Abstract: Background Several metabolites released by fungal species are an essential source of biologically active natural substances. Gas chromatography high resolution time-of-flight mass spectrometry (GC-HRTOF-MS) is one of the techniques used in profiling the metabolites produced by microorganisms, including Talaromyces pinophilus. However, there is limited information regarding differential substrates’ impacts on this fungal strain’s metabolite profiling. This study examined the metabolite profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…These taxonomic descriptive features were used as the initial criteria for fungal identification. Similar features have been reported in previous studies by Ekwomadu et al, 2018 , Adelusi et al, 2022 , Khan et al, 2020 , Thathana et al, 2017 and Compaoré et al (2021) . However, it was acknowledged that the isolation and morphological identification were insufficient to fully establish the fungal isolate's identity at species level.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These taxonomic descriptive features were used as the initial criteria for fungal identification. Similar features have been reported in previous studies by Ekwomadu et al, 2018 , Adelusi et al, 2022 , Khan et al, 2020 , Thathana et al, 2017 and Compaoré et al (2021) . However, it was acknowledged that the isolation and morphological identification were insufficient to fully establish the fungal isolate's identity at species level.…”
Section: Resultssupporting
confidence: 91%
“…The A. flavus strain VKMN22, utilized in this study was isolated from the maize grain samples purchased from a local shop in Johannesburg, South Africa. The fungal species were identified through macroscopic and microscopic methods using the identification method described by Adelusi et al (2022) and subsequently confirmed via molecular analysis. Genomic Deoxyribonucleic acid (DNA) was extracted from each isolate using the Bacterial/Fungal DNA Extraction Kit (Zymo Research, D6005, Irvine, California, USA) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…These three genera share similarities in exometabolites such as proteins, carbohydrates, lipids, and morphological features. They are holophyletic in a cladistic sense and polythetic in an anagenetic or functional purpose (Frisvad, 2015;Adelusi et al, 2022).…”
Section: Molecular Composition Of Exometabolites From Typical Fungal ...mentioning
confidence: 99%
“…T. pinophilus , is also used in the production of bioactive metabolites including alkaloids, esters, furanosteroids lactones, polyketides, terpenoids, and tetraenes ( Li et al, 2017 ; Vinale et al, 2017 ; Zhai et al, 2016 ). Recently, new metabolites were reported including alkanes, amides, aromatic compounds, fatty acids, furans, ketones, acetic acid, 9-octadecenamide, hydrazine, hexadecane, nonadecane, eicosane and undecanoic acid methyl ester, with antimicrobial, antioxidant and anti-inflammatory properties and widely used as plant growth promoters and as biofuel ( Adelusi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%